A Review Of The Chemistry, Electrochemistry And Kinetics Of The Gold Thiosulfate Leaching Process (The Minerals, Metals and Materials Society, 2003)
Environmental and public concerns and the banned use of cyanide for the recovery of gold in some parts of the world have heightened the search for an alternative lixiviant to cyanide. Thiosulfate appears to be the most promising alternative to cyanide due to thiosulfate being non-toxic, relatively cheap compared to cyanide and generally gold recoveries are similar to those of cyanide. The most widely researched thiosulfate process is one where copper ions and ammonia are added to the solution. This paper reviews the leaching of gold in thiosulfate solutions and the contributions of the research at Monash University to the understanding of the gold oxidation reaction in thiosulfate solutions, the solution chemistry when copper ions, ammonia and oxygen are present, the influence of the changing solution chemistry on the gold leach kinetics, and the application of thiosulfate in the leaching of gold from ores. It is clearly shown that the gold oxidation rate is hindered in thiosulfate solutions. In the presence of copper ions the gold oxidation rate though is significantly enhanced and thus is why copper(II) is more effective than other oxidants in the thiosulfate leach system. The copper-ammonia-thiosulfate leach solution chemistry is shown to be very complex, especially in the presence of oxygen as the rate of thiosulfate oxidation increases and the majority of the copper ions are not maintained in the copper(II) oxidation state. The thiosulfate oxidation rate must also be maintained low as an intermediate thiosulfate oxidation product hinders gold leaching. In optimising the recovery of gold from ores with copper-ammonia-thiosulfate leach solutions it is important to evaluate and minimise any negative effect an ore may have on the leach solution chemistry and hence gold leaching.